Addressing chronic wasting disease in Korean farms: topsoil removal and 2N NaOH treatment before cervid restocking - Kyung-Je Park; Hoo-Chang Park; Yu-Ran Lee; In-Soon Roh; Gordon Mitchell; Young Pyo Choi; Hyun-Joo Sohn (Prion, 2025)
Chronic wasting disease (CWD) is a highly contagious prion disease occurring in free-ranging and farmed cervids. In the Republic of Korea, cases of CWD continue to be detected almost annually, on both new and occasionally previously infected farms. CWD-infected animals contaminate soil and other environmental components by shedding prions through their excreta. Since shed prions remain infectious for years in the environment, they can act as infectivity reservoirs facilitating horizontal transmission of CWD. To prevent the further spread of CWD and allow farms to resume operations, control measures on infected farms, including topsoil removal and thorough environmental treatment with 2N NaOH, have been implemented in the Republic of Korea. Restocking remediated farms with cervids was permitted after confirming the absence of prion seeding activity in soil samples using protein misfolding cyclic amplification (PMCA). A total of 215 samples from 18 remediated farms were collected and analysed using PMCA, with only 3 samples from 3 farms displaying prion seeding activity. While the disease control measures effectively eliminated prion seeding activity in CWD-affected farms, CWD recurred at two of the 18 remediated farms 4 to 5 years after restocking animals. It remains unclear whether the recurrence of CWD at the two farms was due to residual prions in the environment after the control measures, or the introduction of the infected animals from other farms. This uncertainty is heightened by the annual occurrence of CWD at multiple farms and the absence of a traceability system for farmed cervids.